Accurate Accounting Recording System And Internal Control In Mr. Agu Dump Truck Rental Services - Androni Susanto; Widya Widya (ConCEPt - Conference on Community Engagement Project, 2023)
Agu Dump Trucks Rental Services has been established since 1990 but because of the lack of system that record transactions accurately, the business is hard to produce report that inform the financial condition of business and making difficulties to owners to make decisions in developing their business. The financial record system owned by Agu Dump Trucks Rental Services is still traditionally manual that causing slow data processing and ineffective preparation of financial reports. The method used in the implementation of this practical work is using primary data sources, where the data needed is directly obtained from related parties. The output result of the implementation of an accounting recording system are statement of financial position, income statement, statement of changes in capital, report on purchases and sales, and report on remaining debts and receivables. The recommendation for future student creativity program is to find the needed place which we can implement for good and correct accounting recording procedures.